Atlas of clinical gynecology. Vol. III, Reproductive endocrinology - Mishell, Daniel R; Stenchever, Morton A (Current Medicine, 1999)
(Current Medicine, Inc.) Provides clinicians and residents with information on reproductive endocrine disorders and infertility. Includes color photos, flow charts, tables, and images. Complete in five volumes. DNLM: Gonadal Disorders--diagnosis atlases.
Keywords: rozmnožování; Menstruation Disturbances; Reproduction; infertilita; rodičovství plánované; poruchy gonád; gynekologie a porodnictví; Infertility; reprodukční techniky; Reproductive Techniques; Gonadal Disorders; reprodukční lékařství; menstruační poruchy; endokrinologie